THE ANALYSIS OF STUDENTS' ERROR IN STRESS PLACEMENT IN ENGLISH PRONUNCIATION OF THE FOURTH SEMESTER STUDENTS AT THE ENGLISH EDUCATION DEPARTMENT IN BORNEO TARAKAN UNIVERSITY - Pebriani, Indah; Rianto, Agus (Universitas Borneo Tarakan, 2023)
The purpose of this research was to find out the error in stress on English by students in the fourth semester of the English Education Department, University of Borneo Tarakan. Purposive sampling was used to choose 30 English Language Education students who were enrolled in the English Morphology course as the study’s participants. This research used a qualitative descriptive method. The data was gathered via a reading test by having the researcher record participants’ accented speech and compare it to the eighth edition of the Oxford Advanced Learner’s Dictionary. The results of the reading test were presented in the form of percentages with a descriptive explanation. The results of this research showed that the students made the most mistakes in pronouncing words with four syllables and that the students had a good level of English pronunciation knowledge. The study also discovered that the number of syllables had an impact on the frequency of errors, as evidenced by data that revealed that more errors were made in words with more syllables than before. Misplaced word stress and double-stressed words were the most common causes of errors in this research.